Cohomological field theory in the BV formalism - Burbano Aldana, Ivan Mauricio [UNESP] (Universidade Estadual Paulista (Unesp), 2020)
O formalismo de Batalin e Vilkovisky (BV) é um dos principais ingredientes de muitas das abordagens que temos para formulações matematicamente precisas de teoria quântica de campos (QFT) perturbativa. Vamos expor este formalismo através de uma reinterpretação cohomologica da equação de Schwinger-Dyson para uma teoria sem simetria de calibre. Isto nos levará a um ponto de vista alternativo das integrais de caminho. Seguindo em analogia com teorias de calibre, vamos codificar de maneira cohomológica as equações de movimento e a estrutura de calibre de teorias clássicas de campos. Os complexos de cocadeias resultantes vão ter como diferenciais os campos vetoriais Hamiltonianos de uma extensão BV da ação. Fixar o calibre nesta nos levará aos análogos quânticos dos complexos clássicos. Os elementos algébricos relevantes vão ser discutidos no contexto de ``toy theories'' de dimensão finita. Com estas vamos poder proceder de maneira análoga ao formalismo BV de uma partícula relativística, teoria de Yang-Mills, teoria de Chern-Simons, e teoria BF.

The Batalin-Vilkovisky (BV) formalism is a major ingredient in several approaches towards mathematically sound formulations of perturbative quantum field theory (QFT). We will develop this framework by interpreting the Schwinger-Dyson equation for a theory without gauge symmetries in a cohomological fashion. This will lead us to an alternative point of view towards path integration. Mirroring this construction for gauge theories we will be able to encode the equations of motion and the gauge structure of classical field theories cohomologically. The differentials of the resulting cochain complexes will be Hamiltonian vector fields for an extended BV action. We will describe a method to gauge fix this action and obtain a quantum theory. The lifting of gauge invariance to the quantum theory will lead us to the quantum analogues of the classical cochain complexes we constructed. The relevant algebraic elements of this formalism will be developed in the simple case of finite dimensional QFT analogues. These will allow us to proceed by analogy to the BV treatment of the relativistic particle, Yang-Mills theory, Chern-Simons theory, and BF theory.
Teoria de campos cohomológica no formalismo BV
Keywords: BV formalism; Gauge symmetry; Odd symplectic spaces; Cohomology; Física matemática; Campos de calibre (Física); Homologia (Matemática)